Avaliação da qualidade das águas na sub-bacia hidrográfica do Rio Siriri/SE - Gonçalves, Amanda de Azevedo (2016)
The sub-basin of the river Siriri stands out for its diversity in land use and soil, having: agricultural activity, with planting of sugarcane and pasture; industrial, producing fertilizers and agro-energy; and urban areas. Also in the study area are perceived visual impacts, such as the removal of riparian vegetation along the river and around the springs reflecting the environmental quality loss; advanced erosion stage in some reaches; sediment banks in bed; odor and the presence of solid waste in dried periods. This study aims to evaluate the quality of surface waters in the watershed of the Rio Siriri by collecting water samples, laboratory tests and statistical tools, in order to contribute to the understanding of its seasonal variation. Thus, to characterize the water quality of the river Siriri were selected five points for the collection of water samples. This research used some statistical tools, such as the descriptive statistics applied to twelve variables: T, pH, DO, N, NO-3, P, chlorophyll-a, PRD, TDS, turbidity, EC and TTC; and the correlation matrix tool; analysis of variance and principal component analysis. The survey showed that DO is on alert for noble uses in this basin in study. P is not within the limit of CONAMA Resolution 357/2005 for Class 1, but within the limit for Class 2, but on alert. There is a negative correlation between the variable agriculture area with the DO and positively with EC, turbidity and P. In the ANOVA analyses, there was significant difference (at 5% level of significance) to the location factor for the variables pH, EC, TDS, DO, turbidity, N, P, TTC, depth, agriculture and pasture. For seasonality factor it was observed significant difference for T, NO-3, N, P, PRD, turbidity, chlorophyll-a and precipitation. By PCA with Varimax rotation, the PC1 (27%) concentrated the variables related to the influence of agricultural activities (EC, TDS, DO, P, agriculture and pasture). It was observed that the point P1 contributed to the variations of N, NO-3 and DO.